Stabilizing mandibular complete dentures by a single midline implant-influence on quality of life: 2-year results from a randomized clinical trial comparing different loading protocols - Abou-Ayash, Samir; von Maltzahn, Nadine; Passia, Nicole; Freitag-Wolf, Sandra; Reissmann, Daniel R.; Luthardt, Ralph G.; Mundt, Torsten; Rädel, Michael; Rammelsberg, Peter; Wolfart, Stefan; Kern, Matthias (Clinical oral investigations, 2019)
The knowledge about the influence of dental treatment on health-related quality of life (HRQoL) is still limited. The aim of this multicenter randomized controlled clinical trial was to assess the effect of stabilizing an existing complete denture, by means of a single mandibular implant, on HRQoL. Furthermore, the impact of the loading protocol, i.e., immediate or delayed loading, in edentulous patients was evaluated.